2014
DOI: 10.1089/jcr.2013.0029
|View full text |Cite
|
Sign up to set email alerts
|

Eveningness Chronotype, Daytime Sleepiness, Caffeine Consumption, and Use of Other Stimulants Among Peruvian University Students

Abstract: Objectives: The aims of this study were to evaluate patterns of circadian preferences and daytime sleepiness, and to examine the extent to which the consumption of stimulant beverages is associated with daytime sleepiness and evening chronotype among Peruvian college-age students. Methods: A total of 2,581 undergraduate students completed a self-administered comprehensive questionnaire that gathered information about sleep habits, sociodemographic and lifestyle characteristics, and the use of caffeinated bever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
4
37
2
7
Order By: Relevance
“…Penolazzi et al (2012) found that the timing of caffeine consumption is also important, and reported that morning-type individuals consume more caffeine in the morning and evening-type individuals consume more caffeine in the evening. However, other studies have found that evening chronotype is not associated with the consumption of caffeinated beverages in the morning or in the evening (Wilson 1990), nor after adjusting for age, sex, cigarette smoking, body mass index, and physical activity (Whittier et al 2014).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Penolazzi et al (2012) found that the timing of caffeine consumption is also important, and reported that morning-type individuals consume more caffeine in the morning and evening-type individuals consume more caffeine in the evening. However, other studies have found that evening chronotype is not associated with the consumption of caffeinated beverages in the morning or in the evening (Wilson 1990), nor after adjusting for age, sex, cigarette smoking, body mass index, and physical activity (Whittier et al 2014).…”
Section: Resultsmentioning
confidence: 86%
“…of several studies suggest that compared to morning-type individuals, evening-type individuals consume more alcohol and smoke more cigarettes (Ishihara et al 1985;Randler 2008;Tran et al 2014;Whittier et al 2014) and have a higher caffeine intake (Adan 1994;Ishihara et al 1985;Mitchell and Redman 1993;Tran et al 2014;Zhang et al 2018). Penolazzi et al (2012) found that the timing of caffeine consumption is also important, and reported that morning-type individuals consume more caffeine in the morning and evening-type individuals consume more caffeine in the evening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for this delayed chronotype is unknown, though it has been speculated that adolescents may exhibit enhanced sensitivity to phase-delays and/or reduced sensitivity to phase-advances compared to adults (Hagenauer et al, 2009). Many studies correlate a high “eveningness” / low “morningness” profile (peak alertness occurring in the evening rather than the morning hours) with use of alcohol and other drugs (Kanerva et al, 2012, Robinson et al, 2013, Tavernier and Willoughby, 2014, Taylor et al, 2011, Urban et al, 2011, Watson et al, 2013, Whittier et al, 2014) as well as addiction (Kervran et al, 2015, Lemoine et al, 2013). This correlation is further accentuated within adolescent and college-age populations (Tavernier and Willoughby, 2014, Taylor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…También se ha propuesto que la activación de las vías inflamatorias por el sueño de corta cantidad puede estar implicada en el desarrollo de obesidad (19) . Las bebidas con cafeína, especialmente café y bebidas energéticas, el tabaco y el alcohol, presentan un consumo elevado en estudiantes universitarios y sus efectos negativos sobre los patrones de sueño se ha documentado en diversos estudios (20) . En nuestro estudio, el consumo de alcohol durante el fin de semana abarcó a un 28,5% mientras que el consumo de tabaco alcanzó un 31,6% de los estudiantes.…”
Section: Referencias Bibliográficasunclassified